Geolocation with respect to personal privacy for the Allergy Diary app - a MASK study - Samreth, D. (2018)
Collecting data on the localization of users is a key issue for the MASK (Mobile Airways Sentinel networK: the Allergy Diary) App. Data anonymization is a method of sanitization for privacy. The European Commission's Article 29 Working Party stated that geolocation information is personal data.To assess geolocation using the MASK method and to compare two anonymization methods in the MASK database to find an optimal privacy method.